1999
DOI: 10.1016/s0029-7844(99)00248-3
|View full text |Cite
|
Sign up to set email alerts
|

Anal sphincter tears at vaginal delivery: risk factors and clinical outcome of primary repair

Abstract: Several risk factors for sphincter tear were identified. Sphincter tear at vaginal delivery is a serious complication, and it is frequently associated with anal incontinence. Special attention should be directed toward risk factors for this complication. Symptoms of anal incontinence should explicitly be sought at follow-up after delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
127
2
11

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(149 citation statements)
references
References 27 publications
9
127
2
11
Order By: Relevance
“…Others studying incontinence at 3-12 months or at 1-5 years after primary repair of an obstetric sphincter tear found similar results with 40-59% of the women having anal incontinence 2,6,9,11,12,21 . In our study the incontinence score increased with time.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Others studying incontinence at 3-12 months or at 1-5 years after primary repair of an obstetric sphincter tear found similar results with 40-59% of the women having anal incontinence 2,6,9,11,12,21 . In our study the incontinence score increased with time.…”
Section: Discussionmentioning
confidence: 75%
“…According to published studies, most women with anal incontinence after an obstetric sphincter tear are incontinent for gas only (gas incontinence/stool incontinence ratio of 5 : 1) 8,12,21,28 . In a 30-year retrospective study of women in three groups (obstetric anal sphincter tear, episiotomy, Cesarean delivery) 16 a surprisingly large number of middle-aged women had anal incontinence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from Sweden reported that prelabor intervention (induction of labor) if the expected birth weight was more than 4000 g was prevalent [13]. As a result of complications due to LGA or the risk factors that lead to induction of labor for LGA babies, there was an increased risk of cesarean sections, of frequent use of episiotomy, or instrumental delivery and of the increased perineal rupture [10,11,14,15]. Therefore, the objectives of this study were to describe the change in the rate of LGA from 1996 to 2010 in India and to study the association between specific maternal risk factors for LGA.…”
Section: Introductionmentioning
confidence: 99%
“…The reported frequency of incontinence of stool in primiparous women ranges from 2 to 6% [MacArthur et al, 1997;Donnelly et al, 1998], and incontinence for either stool or £atus from 13 to 25% [Zetterstrom et al, 1999;Signorello et al, 2000]. After severe perineal laceration, the rate of anal incontinence rises to between 17 and 62% [Crawford et al, 1993;Sultan et al, 1993;Eason et al, 2002].…”
Section: Introductionmentioning
confidence: 99%